Evaluation of cell disruption technologies on magnetosome chain length and aggregation behaviour from Magnetospirillum gryphiswaldense MSR-1 - Masó-Martínez, Marta; Fryer, Benjamin; Aubert, Dimitri; Peacock, Benjamin; Lees, Rebecca; Rance, Graham A.; Fay, Michael W.; Topham, Paul D.; Fernández-Castané, Alfred (Frontiers in Bioengineering and Biotechnology, 2023)
Magnetosomes are biologically-derived magnetic nanoparticles (MNPs) naturally produced by magnetotactic bacteria (MTB). Due to their distinctive characteristics, such as narrow size distribution and high biocompatibility, magnetosomes represent an attractive alternative to existing commercially-available chemically-synthesized MNPs. However, to extract magnetosomes from the bacteria, a cell disruption step is required. In this study, a systematic comparison between three disruption techniques (enzymatic treatment, probe sonication and high-pressure homogenization) was carried out to study their effect on the chain length, integrity and aggregation state of magnetosomes isolated from Magnetospirillum gryphiswaldense MSR-1 cells. Experimental results revealed that all three methodologies show high cell disruption yields (>89%). Transmission electron microscopy (TEM), dynamic light scattering (DLS) and, for the first time, nano-flow cytometry (nFCM) were employed to characterize magnetosome preparations after purification. TEM and DLS showed that high-pressure homogenization resulted in optimal conservation of chain integrity, whereas enzymatic treatment caused higher chain cleavage. The data obtained suggest that nFCM is best suited to characterize single membrane-wrapped magnetosomes, which can be particularly useful for applications that require the use of individual magnetosomes. Magnetosomes were also successfully labelled (>90%) with the fluorescent CellMask™ Deep Red membrane stain and analysed by nFCM, demonstrating the promising capacity of this technique as a rapid analytical tool for magnetosome quality assurance. The results of this work contribute to the future development of a robust magnetosome production platform.